2019
DOI: 10.3390/en12122360
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Production of Lignin, Fatty Acid Methyl Esters and Biogas from Spent Coffee Grounds via an Integrated Physicochemical and Biological Process

Abstract: Spent coffee grounds (SCG) are one of the lignocellulosic biomasses that have gained much attention due to their high potential both in valorization and biomethane production. Previous studies have reported single processes that extract either fatty acids/lignin or biogas. In this study, an integrated physicochemical and biological process was investigated, which sequentially recovers lignin, fatty acid methyl esters (FAME) and biogas from the residue of SCG. The determination of optimal conditions for sequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Sołowski et al ( 2020b ) observed the presence of coinciding with these two gases. Lee et al ( 2019 ) observed common hydrogen sulphide emission in anaerobic digestion. Shivasankaran et al ( 2020 ) discerned that this emission occurs mostly in high protein substrate due to the necessity of breaking amino acids with sulphur during fermentation.…”
Section: Resultsmentioning
confidence: 99%
“…Sołowski et al ( 2020b ) observed the presence of coinciding with these two gases. Lee et al ( 2019 ) observed common hydrogen sulphide emission in anaerobic digestion. Shivasankaran et al ( 2020 ) discerned that this emission occurs mostly in high protein substrate due to the necessity of breaking amino acids with sulphur during fermentation.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the utilization of SCG for productions of bioethanol, butanol, fertilizers and SCG-based sorbent materials for metal removal has been proposed. [3][4][5][6][7] Spent coffee ground is also used for development of skin-whitening products due to its inhibition of tyrosinase activity and melanin synthesis. [8,9] Sufficient amounts of dietary fiber, protein, lipid, and low glycemic sugars in SCG and acceptable rheological properties of SCG-supplemented dough give rise to its application in biscuit products.…”
Section: Introductionmentioning
confidence: 99%
“…Afterwards, the extractives were converted to fatty acids (fatty acids methyl esters and omega-3 fatty acids). 23,24…”
Section: Why Is Organosolv a Valuable Process?mentioning
confidence: 99%